Sintesis Surfaktan Lauroil Etanolamida Berbasis Palm Kernel Oil (PKO) Sebagai Surfaktan Ramah Lingkungan - Birnomianta Sitepu; Rizki Hidayat; Tazkiatun Naf Azzahra; Herawati Oktavianty (Universitas Islam Raden Rahmat, Malang, 2024)
This study aims to synthesize lauric acid from PKO which is then used in the synthesis of lauroyl ethanolamide with variations in synthesis temperature and the ratio of monoethanolamine to lauric acid. The stages of the process carried out include the synthesis of lauric acid and its characterization, the synthesis of lauroyl ethanolamide by varying the synthesis temperature (55, 65, 76 °C), and the mole ratio of lauric acid: monoethanolamine (1:4, 1:6, 1:8) for further surface tension testing and FT-IR testing. The results showed that lauric acid was successfully synthesized, marked by the presence of carbonyl groups (C=O), -OH, C-C, and C-H in the FT-IR test. The synthesis of Lauroyl Ethanolamide was successfully carried out, indicated by the FT-IR test where the C-N, C=O, and C-H groups were present as the forming groups. The surface tension approaching the standard Lauroyl Ethanolamine was produced with a variation in synthesis temperature of 65ºC and a mole ratio of lauric acid: monoethanolamine (1:8) with a surface tension value of 50.87 Dyne/cm.